Determinan Pengetahuan Produk Tabungan Dan Kualitas Pelayanan Terhadap Kepuasan Nasabah Pada Bank BPR NBP 12 Serpong - Nisa Nurafifah; Sugeng Widodo (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
This study aims to examine how savings product knowledge and service quality impact customer satisfaction at Bank BPR NBP 12, Serpong Branch. The study employed quantitative methods through questionnaire distribution. Data analysis included validity and reliability tests, classical assumption tests, multiple linear regression, correlation tests, determination tests, t-tests, and F-tests using SPSS. The t-test results indicate that the Product Knowledge (X₁) variable has a significance value of 0.020 (<0.05), thus having a positive and significant effect on Customer Satisfaction. The Service Quality (X₂) variable has a significance value of 0.000 (<0.05), indicating a positive and significant effect on Customer Satisfaction and a more dominant variable. The F-test results show a calculated F value of 56.404 with a significance value of 0.000 (<0.05), indicating that Product Knowledge and Service Quality simultaneously have a significant effect on Customer Satisfaction. The R² value of 0.567 indicates that 56.7% of customer satisfaction can be explained by the two variables. Simultaneous testing shows that both variables together have a significant effect on customer satisfaction (sig. 0.000). In short, improving service quality and understanding of savings products can increase customer satisfaction at Bank BPR NBP 12 Serpong Branch